Pertanggungjawaban Hukum Pemerintah Kota Cirebon dalam Penanggulangan Bencana Banjir Berdasarkan Undang-Undang Nomor 24 Tahun 2007 - Muhamad Rayhan Salman; Agus Dimyati (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the legal responsibility of local governments in flood disaster management in Kalijaga Village based on Law Number 24 of 2007 and identify obstacles faced in its implementation. The study uses an empirical legal method with analytical descriptive specifications through literature studies and interviews. The results of the study indicate that the Cirebon City Government has carried out legal responsibilities through mitigation, preparedness, emergency response, rehabilitation and inter-agency coordination activities, but its implementation has not been optimal because flooding still occurs repeatedly. Obstacles faced include limited budget, facilities and infrastructure, spatial planning, cross-sector coordination, community participation and high rainfall. The need for strengthening mitigation, improving infrastructure and synergy of all stakeholders is needed.